Crosstalk between epithelium, myeloid and innate lymphoid cells during gut homeostasis and disease - Ghilas, Sonia; O’Keefe, Ryan; Mielke, Lisa Anna; Raghu, Dinesh; Buchert, Michael; Ernst, Matthias (Frontiers in Immunology, 2022)
The gut epithelium not only provides a physical barrier to separate a noxious outside from a sterile inside but also allows for highly regulated interactions between bacteria and their products, and components of the immune system. Homeostatic maintenance of an intact epithelial barrier is paramount to our health, requiring an intricately regulated and highly adaptive response of various cells of the immune system. Prolonged homeostatic imbalance can result in chronic inflammation, tumorigenesis and inefficient antitumor immune control. Here we provide an update on the role of the intraepithelial lymphocytes, innate lymphoid cells, macrophages and dendritic cells, which play a critical role in epithelial barrier maintenance and provide important linkage between the classical innate and adaptive arm of the immune system. These interactions regulate the capacity of the gut epithelium to undergo continuous renewal, safeguard against tumor formation and provide feedback to the gut microbiome as a seminal layer of homeostasis across all cell types in the gut.